Advancing Arbitration for Multinational Construction Projects in Saudi Arabia Through Flexibility and Legal Reforms - Abdul Rub, Khalid; Elwakeel, Adam; Al-ghamdi, Malik (International Journal of Law and Public Policy (IJLAPP), 2024)
The role of arbitration in resolving multinational construction disputes in Saudi Arabia is explored, focusing on procedural flexibility, confidentiality, and the impact of recent legal reforms. Multinational companies prefer arbitration over traditional litigation due to its closed process, which protects sensitive information—crucial in Saudi Arabia's privacy-focused business environment. Using qualitative methods like case studies, interviews, and legal document analysis, the research highlights key themes such as the need for arbitrators with technical expertise and cultural understanding, enhancing the arbitration process. Confidentiality is a major factor in choosing arbitration, offering protection from public exposure. Additionally, arbitration’s procedural flexibility allows for customized solutions, leading to faster dispute resolution. Legal reforms, including the Saudi Arbitration Law 2012 and the Saudi Center for Commercial Arbitration (SCCA), have strengthened the arbitration framework, boosting investor confidence and improving efficiency. Future research should examine the long-term impact of these reforms, assess the effectiveness of new arbitration institutions, and explore challenges in maintaining confidentiality and selecting competent arbitrators across sectors.